Pelatihan Staf Untuk Mencapai Visi Dan Misi Perusahaan - Zuhri Arsyadani (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
The current world of work (business) not only requires academic and professional abilities (hard skills), but also internal and interpersonal abilities (soft skills). Soft skill competency is very important because many companies or institutions not only need human resources who are intelligent and able to handle the tasks given. Companies and agencies want human resources (HR) who are able to communicate, communicate, are hard workers, intelligent, adapt easily to the work environment and are able to collaborate with colleagues and superiors. Human resource (HR) skills must always be updated to face increasing competition. tight in Era 4.0. Competency can be improved by combining hard skills and soft skills as well as two hard skills and soft skills. PT employee training (training). Increasing the competency of employees (employees) must really be carried out in a planned, directed and sustainable manner to increase professional capacity and skills. Improving the quality of personnel means increasing operational capabilities in carrying out real work tasks Keywords: HR, Soft Skills, Hard Skills